The Role of Word of Mouth and Digital Media in Increasing Promotion Effectiveness - Yuyun Wahyudi; Sukaris Sukaris (Advances in Business & Industrial Marketing Research, 2026)
Purpose: This study analyzes the role of Word of Mouth (WoM) and digital media in enhancing promotional effectiveness at PT. Gresik Anugrah Sejahtera in a B2B industrial service context. Research Method: A qualitative descriptive case study was conducted using purposive sampling. Data were collected through interviews with management and business partners, direct observation, and company documentation. Data analysis applied data reduction, display, and conclusion drawing with source triangulation. Results and Discussion: Findings show that WoM is crucial in maintaining trust, loyalty, and demand stability, but its impact is limited to existing networks. Digital media is utilized but not strategically managed, resulting in limited contribution to market expansion. Lack of integration between WoM and digital media leads to defensive promotional practices. Implications: Companies should integrate WoM and digital media to improve promotional effectiveness and competitiveness. Future research may apply quantitative or mixed methods. Originality: This study highlights the integration gap between WoM and digital media in B2B industrial services.